Changes in mountain landscape and livestock management in northern Spain: a study in Las Ubiñas-La Mesa Biosphere Reserve (Asturias, NW Spain) - González Díaz J.A.; Fernández García F.; Osoro K.; Celaya R.; Rosa García R. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
Asturias is a region with outstanding biodiversity frequently linked to mountainous areas where traditional activities (mostly animal husbandry) have shaped and maintained diverse landscapes. Such areas have evolved significantly over the past decades, although our knowledge of the past and present dynamics is clearly limited despite it would be essential for their future management. In addition, the diversity of ecosystems, environmental and socio-cultural conditions present in the Asturian territory demand both global and local approaches. The aim of this study was to analyze the evolution of the landscape in a pastoral area (Puertos de Agüeria) included in Las Ubiñas-La Mesa Biosphere Reserve, a protected area where seasonal transhumance of beef cattle and horses persists, whereas other livestock species (especially small ruminants) have disappeared. The orthorectification and photointerpretation of aerial photographs provided the database for the study of landscape evolution. The changes in landscape were evaluated qualitatively and quantitatively using aerial images from 1956, 1985 and 2011. A progressive impoverishment of the mosaicity is observed together with a structural homogenization. The role of small ruminants in shaping the landscape is discussed. The shrublands and forests increased while grassland areas substantially decreased. Such changes are related to shifts in livestock composition: a progressive disappearance of sheep and goats towards a dominance of cattle and horses.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)